Jihadi fiction: radicalisation narratives in the contemporary novel. Issue 3 (16th April 2017) - Morrison, Jago
ABSTRACT: As Ulrich Beck suggests in World at Risk, fear of Islamist extremism has become a dominant strand in contemporary perceptions of risk. In the media, a set of 'stock' radicalisation narratives have emerged in which, typically, a misguided loner is brainwashed into embracing a violent perversion of Islam. In the background, the wider Muslim community is accused of a dangerous complicity and complacency. This essay explores some notable attempts in fiction to unpick such popular radicalisation narratives. In novels by John Updike and Sunjeev Sahota, the psychological and faith dimensions of suicide bombing are a key focus, attempting to explore from the inside, how an educated young Muslim might be impelled along the path to martyrdom. In texts by Mohsin Hamid and J.M. Coetzee, the ideological staging of 'radicalisation' and 'fundamentalism' themselves is brought into question. Current counterterrorist measures include indefinite detention of US citizens without trial, while in the UK, over two million public sector workers have been recruited to the largest surveillance exercise ever codified in British law. In this context, the essay shows how recent fiction has attempted to trouble the frames of representation through which a perpetual state-of-emergency is passed off as our 'new normal'.